Metod Pengajian Braillle Al-Quran - Ahmad Kamel Mohamed; Muhammad Mustaqim Mohd.Zarif; Khairul Anuar Mohamad; Mohd Alwi Yusoff (Universiti Sains Islam Malaysia, 2024)
This study focuses on identifying and analyzing various issues and aspects relating to the principles and methods of Quranic Braille and its implementation in Malaysia. It aims to develop a suitable curriculum of study, which can be used in teaching and learning a new course offered by the Faculty of Quranic and Sunnah Studies entitled "Aplikasi Braille dalam Pengajian Quran dan Sunnah" starting from semester 11, 2007/2008 academic session. Apart from library research, this study adopts various field study methods such as interviews, observation, and opinion survey through the use of survey questionnaires as its main instruments for data collection. This is due to the difficulty in obtaining written materials on Quranic Braille, and most of the information is gathered directly from the experts who are involved with it for a long period of time. The findings indicate that in order for a comprehensive treatment of the subject matter, the proposed study curriculum must reflect all the available methods of Quranic Braille transcription in Malaysia in terms of their usage, strengths, limitations, and so forth. At the same time, contemporary study of Quranic Braille must also benefit from the latest technology, especially through the use of a certain apparatus and computer softwares which are available in the market.